(untitled) (Journal of Parents and Teachers, 2014)
The Youth 2000 and Religion Report is born of concern for religiosity among youth. The report, which starts from five hypotheses, offers data such as the percentage of young people who receive the Sacrament of Confirmation, who go to mass, who participate in Catholic holidays or the image that the Church has among the young.